The Effect Of Talk English Application On Students' Speaking Aability - Harahap, Fitri Ramadani; Saragih, Butet Marthalina; Nasution, M. Rouzhi Aristha (English Lecturers and Teachers Association (ELTA), 2024)
This study was made to find out the the effect of talk english application on students’ speaking ability. The researcher used experimental research. The sample of this research consisted of 30 students from class XI nursing SMK Kesehatan Ganda Husada Tebing Tinggi. The data obtained of the population by using cluster sampling technique in one class. The pretest used to determine the students' initial speaking ability. The posttest was carried out after the treatment was applied Talk English Application by utilizing the application as a media support in learning English. The data was collected by spoken test as a research data instrument. The technique of data analysis is Two Ways Analysis of Variance (ANNOVA) with significance level P = 0.000 < 0.05. It was found that talk english application on student’ speaking ability was more effective. So the writer suggest to all teachers, especially English teachers, to implement talk english application in the teaching and learning speaking ability. So that students are more active and can think critically both among students and also to teachers. Key words : Talk English Aplication; Speaking Ability